2016
DOI: 10.14445/23488352/ijce-v3i9p101
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Numerical Study of Concrete Filled Tabular Columns

Abstract: Concrete filled steel tabular columns have gained immense importance in recent decades due to numerous structural benefits especially in developed countries like china, Japan, U.S.A, Britain. In this paper analytical equations are put to understand the mechanism of concrete filled tabular columns under axial loading. For this purpose a comparison between design codes Eurocode-4, and AISC-LRFD has been made in evaluating the axial compressive strength of concrete filled tabular columns. This study further prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
0
0
1
Order By: Relevance
“…Os primeiros documentos relatando estudos de pilares mistos preenchidos foram divulgados na década de 1960 (KNOWLES;PARK, 1969) e trazem resultados de ensaios realizados com elementos submetidos a compressão centrada. Desde então, vários estudos teóricos e experimentais vêm sendo realizados; como exemplos citam-se Uy (1998), Hu et al (2003), Sakino et al (2004), Wang et al (2012) e Hafiz (2016). Porém, somente a partir da década de 1990 é que são divulgados os primeiros estudos voltados para a modelagem numérica desses elementos estruturais.…”
Section: Figura 1 -Seção Transversal Característica Dos Pilares Mistos Preenchidosunclassified
“…Os primeiros documentos relatando estudos de pilares mistos preenchidos foram divulgados na década de 1960 (KNOWLES;PARK, 1969) e trazem resultados de ensaios realizados com elementos submetidos a compressão centrada. Desde então, vários estudos teóricos e experimentais vêm sendo realizados; como exemplos citam-se Uy (1998), Hu et al (2003), Sakino et al (2004), Wang et al (2012) e Hafiz (2016). Porém, somente a partir da década de 1990 é que são divulgados os primeiros estudos voltados para a modelagem numérica desses elementos estruturais.…”
Section: Figura 1 -Seção Transversal Característica Dos Pilares Mistos Preenchidosunclassified
“…steel yielding or concrete crushing), the CFHS stub column reaches its ultimate capacity, at which point both the concrete core and steel section reach their strength limits. Hafiz [2] examined the experimental and numerical simulation results and found that a CFHS column under axial compression load is not affected by a change in length. The experimental results may be primarily influenced by the confinement effect and the contribution of the steel section [3].…”
Section: Introductionmentioning
confidence: 99%